A Technique for Chromosome Count Faom Developing Leap Buds of Induced Tetraploid and Diploid Samalum aleum .L - Kapoor, M. L. (Indian Forester, 1981)
Best results were achieved for cytological preparation from developing leaf buds of S. album when fixed in modified Cornoy’s solution having from Chlorlde in traces hydrolysed in 1 : 9 parts of Normal Hcl and Aceto-orcein and stained in 2% Aceto-orcein. Chromosome number of diploid (2n = 20) and induced tetraploid (4n = 40) was counted by this techaiquea from leaf bads fixod at 1l.30 A.M. The induced tetraploids did not show the reversion trend to diploidy. Flowering is delayed in tetraploid.